Frei Caneca: matriz do jornalismo brasileiro - Carvalho, Tatiane Eulália Mendes de (2011)
Analyzing the rhetoric built by Frei Caneca and rebuild his thinking communication, arguing that the activity developed in the press credence as array of Brazilian journalism, are the objectives of this search. This is an exploratory study, supported by bibliographic and documentary sources, with the intention to understand the historical context of the rhetoric an the Brazilian journalism the. To characterize the journalism practiced Frei Caneca was applied mixed methods - qualitative and quantitative - of the content analysis. The Results indicate that Frei Caneca, by the rhetoric, began producing a structured argumentative journalism, because his writing had a theoretical basis. In this way, contributed to the advance of studies of the Journalism Theory to make reading a Brazilian rhetoric and eloquence.